Sediment Characteristics of Mergui Basin, Andaman Sea based on Multi-proxy Analyses - Rina Zuraida; Rainer Arief Troa; Marfasran Hendrizan; Luli Gustiantini; Eko Triarso (BULLETIN OF THE MARINE GEOLOGY, 2017)
This paper presents the characteristics of sediment from core BS-36 (6°55.85’ S and 96°7.48’ E, 1147.1 m water depth) that was acquired in the Mergui Basin, Andaman Sea. The analyses involved megascopic description, core scanning by multi-sensor core logger, and carbonate content measurement. The purpose of this study is to determine the physical and chemical characteristics of sediment to infer the depositional environment. The results show that this core can be divided into 5 lithologic units that represent various environmental conditions. The sedimentation of the bottom part, Units V and IV were inferred to be deposited in suboxic to anoxic bottom condition combined with high productivity and low precipitation. Unit III was deposited during high precipitation and oxic condition due to ocean ventilation. In the upper part, Units II and I occurred during higher precipitation, higher carbonate production and suboxic to anoxic condition.Keywords: sediment characteristics, Mergui Basin, Andaman Sea, suboxic, anoxic, oxic, carbonate content Makalah ini menyajikan karakteristik sedimen contoh inti BS-36 (6°55,85’ LS dan 96°7,48’ BT, kedalaman 1147,1 m) yang diambil di Cekungan Mergui, Laut Andaman. Metode analisis meliputi pemerian megaskopis contoh inti, pemindaian contoh inti dengan menggunakan multi-sensor core logger, dan pengukuran kandungan karbonat. Tujuan penelitian adalah untuk mengetahui karakteristik fisik dan kimiawi sedimen untuk menafsirkan kondisi lingkungan pengendapan. Hasil penelitian menunjukkan bahwa contoh inti ini dapat dibagi menjadi 5 unit litologi yang mewakili kondisi lingkungan yang berbeda. Pada bagian bawah sedimen, Unit V dan IV ditafsirkan sebagai hasil endapan pada kondisi suboksik hingga anoksik pada saat produktivitas tinggi dan curah hujan rendah. Unit III diendapkan pada saat curah hujan tinggi dan kondisi oksik yang diperkirakan berkaitan dengan ventilasi samudera. Pada bagian atas, Unit II dan I diendapkan pada saat curah hujan cukup tinggi dengan produksi karbonat yang cukup besar dan kondisi dasar laut suboksik hingga anoksik. Kata kunci: karakteristik sedimen, Cekungan Mergui, Laut Andaman, suboksik, anoksik, oksik, kandungan karbonat